Combinatorial Study Implementation In Kaggle Applications - Afifah, Nur (Al'Adzkiya, 2022)
One of the core subjects of Mathematics is that students are expected to have the ability to understand concepts, explain the interrelationships between concepts and apply concepts accurately, efficiently and precisely in solving problems. There are many students who, after learning mathematics, are unable to understand even the simplest parts, many concepts are misunderstood so that mathematics is considered a difficult science. Understanding the concept is the most important part in learning mathematics, one of which is in combinatorial material, increasing the understanding of combinatorial concepts needs to be pursued for the success of students in learning. Combinatorial is a branch of mathematics for calculating the number of possible arrangements of objects without having to enumerate all possible arrangements. Kaggle is a site or platform that holds competitions in the field of Data Science, kaggle is also a common (practically) Science learning resource. For this reason, an early introduction to this technology is needed for students who are still in school. Writing this article aims to get an overview of students' understanding of the concepts of combinatorial and kaggle so that students can apply questions about combinatorial to kaggle.